Supramolecular transitions in native cellulose-I during progressive oxidation reaction leading to quasi-spherical nanoparticles of 6-carboxycellulose - Sharma, Priyanka R.; Rajamohanan, Pattuparambil R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Cellulose-I swells considerably in phosphoric acid, and converts to amorphous cellulose via a cellulose-II transition state. Controlled oxidation of cellulose-I to 6-carboxycellulose (6CC) using HNO3-H3PO4-NaNO2 oxidation system led to the selective production of 6CC's of varying carboxyl contents (1.7-22%) as well as various shapes and sizes (macro-sized fibrils of several micron length and/or spherical nanoparticles of 25-35 nm), depending on the reaction conditions. 6CC's having less than 14% carboxyl content were largely in cellulose-II form (WAXRD values in-between cellulose I and cellulose II), whereas at 14-22% the 6CC's were largely amorphous; only trace crystallinity was observed at 19% and 22% carboxyl 6CC. Spherical nanoparticles retained a high degree of crystallinity having cellulose-I structure, whereas the macro-sized fibrils were largely converted to cellulose-II structure. Analysis by WAXRD as well as by CP-MAS C-13 NMR studies gave similar conclusions. Reduced molecular weight with progressive oxidation, including presence of oligomers, was also evident from an increase in the reducing-end carbon peak at similar to 92 ppm. For high oxidation levels (>14%) the NMR 92-96 ppm peaks disappeared on extracting with dilute alkali, due to soluble oligomers being removed. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxycellulose; cellulose; Nanoparticles; NMR; WAXRD